Assessing Cognitive Therapy Skills Comprehension, Acquisition, and Use by Means of an Independent Observer Version of the Skills of Cognitive Therapy (SoCT-IO) - Brown, Gregory K. (Psychol Assess, 2015)
OBJECTIVES: The purposes of this study were (1) to describe the adaptation and psychometric properties of the Skills for Cognitive Therapy (SoCT) measure for use by an independent observer (SoCT-IO) who rates the cognitive therapy (CT) skill acquisition, comprehension, and use by depressed adults and (2) to compare ratings of CT skill comprehension, acquisition, and use by independent observers to those by patients and therapists. METHOD: Like the other SoCT versions, the SoCT-IO consists of 8 items that assess patients’ comprehension, acquisition, and use of cognitive and behavioral skills for managing depressive symptoms, using a 5-point Likert-type scale. Four experienced raters (two doctoral-level CT therapists and two bachelor-level non-therapists) used the SoCT-IO to rate 80 CT videotapes from both mid and later sessions in acute-phase CT from a randomized controlled trial for outpatients with recurrent major depression. RESULTS: The SoCT-IO ratings showed excellent internal consistency reliability and moderately high interrater reliability. Concurrent validity was demonstrated by convergence of the SoCT-IO with two other versions of the SoCT, one completed by therapists (SoCT-O) and the other by patients (SoCT-P). SoCT-IO ratings evidenced good predictive validity: Independent observers’ ratings of patient CT skills mid-phase in therapy predicted treatment response even when the predictive effects of SoCT ratings by therapists and patients were controlled. CONCLUSIONS: The SoCT-IO is a psychometrically sound measure of CT skill comprehension, acquisition and use for rating outpatients with recurrent depression. The clinical utility and implications for using the SoCT-IO as a measure of CT skills acquisition are discussed.